Isolation, Quantification, and Plaque Morphology Analysis of Lytic Bacteriophages from River Water Targeting Clinical MDR Klebsiella pneumoniae Using the Double-Layer Agar Method - Aminah, Aminah; Trisna, Citra; Sugianto, Fitri Alina; Amalia, Gadis; Martiningsih, M Atik; Faruq, Zulfikar Husni (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2025)
Antimicrobial resistance is a growing global health threat and is projected to cause up to 10 million deaths per year by 2050. Klebsiella pneumoniae is a priority pathogen due to its multidrug resistance (MDR) mechanisms, such as extended-spectrum β-lactamases and carbapenemases, which significantly limit therapeutic options and increase the need for antimicrobial alternatives. This study aimed to isolate and quantify active lytic bacteriophages capable of infecting clinical MDR K. pneumoniae from river water samples. Water samples were processed by centrifugation and membrane filtration to remove debris and bacterial cells, then incubated with MDR K. pneumoniae in Luria broth at 37°C to enhance phage adsorption and amplification. Phage detection and enumeration were performed using the double-layer agar method. Plaque morphology was observed to confirm lytic activity, while serial dilutions were used to determine phage titer. Several lytic bacteriophages were successfully isolated from river water samples. The plaques formed were clear, spherical, and well-defined, with some exhibiting halos indicative of possible depolymerase activity. Phage titers ranged from 1.28 × 10³ to 2.00 × 10⁶ PFU/mL, indicating efficient replication against MDR K. pneumoniae without repeated enrichment processes. River water is a potential source of lytic bacteriophages capable of infecting MDR K. pneumoniae. These findings emphasize the role of aquatic environments as natural reservoirs of phages with potential use in the development of future antimicrobial or biocontrol strategies and support the need for further studies on the host range, stability, and therapeutic applications of the isolated phages.